Cdc42 Is Essential for Both Articular Cartilage Degeneration and Subchondral Bone Deterioration in Experimental Osteoarthritis. (15th February 2018) - Hu, Xinhua; Ji, Xing; Yang, Mengting; Fan, Shihao; Wang, Jirong; Lu, Meiping; Shi, Wei; Mei, Liu; Xu, Chengyun; Fan, Xueying; Hussain, Musaddique; Du, Jingyu; et al.
ABSTRACT: Cdc42, a member of Rho family small guanosine triphosphatases (GTPases), is critical for cartilage development. We investigated the roles of Cdc42 in osteoarthritis and explored the potential mechanism underlying Cdc42‐mediated articular cartilage degeneration and subchondral bone deterioration. Cdc42 is highly expressed in both articular cartilage and subchondral bone in a mouse osteoarthritis model with surgical destabilization of the medial meniscus (DMM) in the knee joints. Specifically, genetic disruption of Cdc42, knockdown of Cdc42 expression, or inhibition of Cdc42 activity robustly attenuates the DMM‐induced destruction, hypertrophy, high expression of matrix metallopeptidase‐13 and collagen X, and activation of Stat3 in articular cartilages. Notably, genetic disruption of Cdc42, knockdown of Cdc42 expression or inhibition of Cdc42 activity significantly restored the increased numbers of mesenchymal stem cells, osteoprogenitors, osteoblasts, osteoclasts, and neovascularized vessels, the increased bone mass, and the activated Erk1/2, Smad1/5 and Smad2 in subchondral bone of DMM‐operated mice. Mechanistically, Cdc42 mediates interleukin‐1β–induced interleukin‐6 production and subsequent Jak/Stat3 activation to regulate chondrocytic inflammation, and also lies upstream of Erk/Smads to regulate subchondral bone remodeling during transform growth factor‐β1 signaling. Cdc42 is apparently required for both articular cartilage degeneration and subchondral bone deterioration of osteoarthritis, thus, interventions targeting Cdc42 have potential in osteoarthritic therapy. © 2018 American Society for Bone and Mineral Research.